Development of a settlement prediction model for upper subgrade layers of ballasted tracks. (August 2021) - Park, Jae Beom; Lim, Yujin
Recently, settlement in railway tracks is posing a serious challenge. In particular, ballasted tracks can experience settlement due to repeated dynamic loading and various geotechnical factors such as consolidated settlements of natural foundation soil and poor compaction, which lead to track irregularities. Among these factors, settlement in track foundation has been identified as the primary cause of track irregularities. Such settlement mainly results from permanent deformation, a form of progressive settlement found in the upper subgrade due to the repeated dynamic loading of trains. As such, it is necessary to conduct a behavioral analysis of upper subgrade soil, which is susceptible to permanent deformation. A large-scale finite element analysis was performed using an existing permanent deformation prediction model to analyze the effects of permanent deformation on settlement in underlying soil materials of ballasted tracks. The results were used to propose a prediction model for settlement in the upper subgrade of ballasted tracks. The proposed model allows more accurate predictions of settlement that may occur in the upper subgrade of ballasted tracks, and can also be employed in predicting track irregularities.